Kriminologie in der Zivilgesellschaft : Wissenschaftsdiskurse und die britische Öffentlichkeit, 1830-1945 - Freitag, Sabine (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London ;, 2014)
Why do people become criminals? What causes delinquent behavior? Such questions occupy experts as well as the general public - and there is more reciprocal exchange of ideas between them than one might at first imagine. Sabine Freitag examines both the sites of knowledge production and the spaces in civil society where expert hypotheses are debated.